P222 Health-related quality of life symptom burden after COVID-19. (11th November 2022) - Knight, F; McLeod, N; Akinola, T; Kamal, F
Abstract : Introduction: Patients hospitalised with COVID-19 are susceptible to chronic symptoms that can impact their health-related quality of life (HRQL). There is a limited understanding of the timeline of these symptoms or predictors of poorer HRQL outcomes in this patient cohort. We compared HRQL symptoms; specifically mobility, breathlessness, and anxiety and depression in patients pre- and post- hospitalisation with COVID-19, to identify any predictors of persistent symptoms. Method: 350 patients admitted with COVID-19 to Royal Berkshire Hospital between March 2020 and September 2021 were included. Symptom data was captured using the validated EQ-5D-5L questionnaire with pre-COVID scores (week 0), recorded retrospectively at time of discharge or at 6 weeks, compared with scores at 6- and 12-weeks post hospital discharge. Statistical analyses used a one-tailed dependent t-test to compare scores between the time points and logistic regression examined the influence of comorbidity burden, ICU admission and length of stay. Results: Complete data was available for n=350 (61% male, mean age 57.8 years, SD 12.81). All patients required supplementary oxygen therapy with 79% requiring non-invasive ventilation and 16.62% mechanical ventilation. A statistically significant improvement was found in mobility, breathlessness and anxiety and depression scores at 12 weeks compared to 6 weeks. Overall HRQL scores were lower at week 0 than at week 12 (mean=5.6, SD 2.66 vs. mean=5.78, SD 5.46, p=0.0434), indicating a poorer HRQL outcome at 12 weeks compared to pre-COVID. Thus, the t-test result for the null hypothesis (HRQL at 0 weeks ≤HRQL at 12 weeks) was not statistically significant. There was no statistically significant difference on score outcomes of patients who required ICU compared to ward-based care. Pre-existing pulmonary disease was the only statistically significant risk factor identified to increase breathlessness scores at 12 weeks. Conclusion: Hospitalised patients who survived COVID-19 have impaired HRQL symptoms at 12 weeks compared to their pre-COVID baseline, though were on an improving trajectory. The data highlights that COVID-19 rehabilitation services may need to consider longer programme durations with appropriate psychological and physical support and targeting individuals with pre-existing pulmonary disease may help to address the symptom chronicity. Further research is required to tailor rehabilitation services.